Luteolin delays the progression of IgA nephropathy by attenuating inflammation, oxidative stress and reducing extracellular matrix accumulation through activating the Nrf-2/HO-1 pathway - Liang, Dong-Yu; Cong, Shao-Hua; Li, Lin-Hui; Yi, Qing-Qing; Tang, Li-Ping; Cao, Li-Ou (Frontiers in Pharmacology, 2025)
IgA nephropathy (IgAN) is the most common primary glomerulonephritis and the main cause of end-stage renal disease (ESRD). Luteolin (Lut), which is present in various plants, has anti-inflammatory and antioxidant properties under numerous medical conditions. This study aimed to investigate the therapeutic effects and potential mechanisms of Lut on IgAN. Mouse models of IgAN and HBZY-1 cells stimulated with Gd-IgA1 were used as experimental objects. Renal pathology, inflammation, reactive oxygen species (ROS) levels, and extracellular matrix (ECM) accumulation were measured. The results indicated that Lut improved renal pathological damage, reduced the levels of inflammatory cytokines, decreased ROS levels, and attenuated ECM accumulation. Moreover, Lut promoted the activation of the Nrf-2/HO-1 pathway. Furthermore, blocking Nrf2 reversed the suppressive effects of Lut on inflammation, oxidative stress, and the expression of ECM proteins in mesangial cells stimulated with Gd-IgA1. In conclusion, the protective effect of Lut against IgAN may occur by triggering the Nrf2/HO-1 pathway, thereby suppressing inflammation, oxidative stress, and ECM deposition.